2015
DOI: 10.1007/s00259-015-3157-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of 99mTc-MAA SPECT/CT-based dosimetry in the radioembolization of liver malignancies with 90Y-loaded microspheres

Abstract: Radioembolization with 90Y-loaded microspheres is increasingly used in the treatment of primary and secondary liver cancer. Technetium-99 m macroaggregated albumin (MAA) scintigraphy is used as a surrogate of microsphere distribution to assess lung or digestive shunting prior to therapy, based on tumoral targeting and dosimetry. To date, this has been the sole pre-therapeutic tool available for such evaluation. Several dosimetric approaches have been described using both glass and resin microspheres in hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 50 publications
4
91
0
1
Order By: Relevance
“…The application of segmental treatments significantly improved long-term OS in our cohort supporting the concept of radiation segmentectomy for improved preservation of liver parenchyma, especially in the absence of transplantation [11]. Dosing >200Gy was not associated with improved OS or earlier response consistent with the concept of threshold dose [11,18,19]. Y90 dosing has not been significantly linked to imaging response, survival, or toxicity [16,20,21].…”
Section: Discussionsupporting
confidence: 63%
“…The application of segmental treatments significantly improved long-term OS in our cohort supporting the concept of radiation segmentectomy for improved preservation of liver parenchyma, especially in the absence of transplantation [11]. Dosing >200Gy was not associated with improved OS or earlier response consistent with the concept of threshold dose [11,18,19]. Y90 dosing has not been significantly linked to imaging response, survival, or toxicity [16,20,21].…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, differences in the catheter position cannot be ruled out with certainty but seem quite unlikely and cannot be considered a major confounding issue. This is also supported by the results of Ulrich et al, who did not find any correlation between catheter position, 99m Tc-MAA uptake, and therapy response (6). Second, we experienced only a very limited number of vasospasms during angiography.…”
Section: Replysupporting
confidence: 87%
“…The lower correlation between 99m Tc-MAA and microsphere uptake in non-HCC liver tumors is supported by several studies, partly with high numbers of included patients. Ulrich et al found no significant correlation between response and 99m Tc-MAA uptake in 66 patients with colorectal liver metastases (6). Also, Wondergem et al reported significant differences in 99m Tc-MAA and microsphere uptake (7).…”
Section: Replymentioning
confidence: 99%
“…The main limitation to 90 Y radioembolization, however, is hepatopulmonary shunting of radiotracer and subsequent pulmonary injury. To avoid this complication, pre-procedural planning using 99m Tc-MAA is performed and lung shunt fractions are calculated, with 90 Y dosage adjusted accordingly or radioembolization avoided entirely [1]. …”
mentioning
confidence: 99%